2004
DOI: 10.1021/ie0494263
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of 2,4-Dichlorophenoxyacetic Acid Using Concentrated Solar Radiation:  Batch and Continuous Operation

Abstract: Solar photocatalytic oxidation (PCO) for the degradation of liquid and gaseous pollutants is receiving increasing attention. In the present investigation, an attempt has been made to demonstrate the feasibility of a novel slurry photoreactor for the mineralization of 2,4-dichlorophenoxyacetic acid (2,4-D) by using a semiconductor photocatalyst (TiO2), air, and concentrated solar radiation. The photocatalytic degradation (PCD) of 2,4-D using concentrated solar radiation in both batch and continuous bubble colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 30 publications
(101 reference statements)
2
26
0
1
Order By: Relevance
“…At a high pH level, H 2 O 2 decays fast which forms a barrier to the creation of ·OH radical, and greatly inhibits the decay of 2,4-D (Chu 2001); on the other hand, pH affects the state of ionization of the substrate and, hence, its adsorption to the catalyst. Greater adsorption of 2,4-D was observed under nonionized and low-pH condition (Kwan and Chu 2004;Kamble et al 2004). In this study, the pH is uncontrolled in the reaction system with the initial pH of 3.5.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…At a high pH level, H 2 O 2 decays fast which forms a barrier to the creation of ·OH radical, and greatly inhibits the decay of 2,4-D (Chu 2001); on the other hand, pH affects the state of ionization of the substrate and, hence, its adsorption to the catalyst. Greater adsorption of 2,4-D was observed under nonionized and low-pH condition (Kwan and Chu 2004;Kamble et al 2004). In this study, the pH is uncontrolled in the reaction system with the initial pH of 3.5.…”
Section: Resultsmentioning
confidence: 69%
“…The decay of 2,4-D was also pH dependent. Studies indicated that the highest decay rates of 2,4-D were observed at acidic pH and were followed at basic pH, and the lowest decay rates were observed at neutral pH (Chu 2001;Kwan and Chu 2004;Kamble et al 2004). It is likely, on the one hand, that pH severely affects the self-decomposition of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained with commercial sevnol were consistent with those of pure carbaryl, although the reaction was slower. Other pesticides degraded by photocatalysis include 2,4-dichlorophenoxyacetic acid (2) and 3-(3,4-dichlorophenyl)-1,1-dimethylurea or diuron (5) (a phenylurea pesticide) (Malato et al 2003;Kamble et al 2004). …”
Section: Pesticidesmentioning
confidence: 99%
“…Previously, it was demonstrated that the alkoxyl radical anion (-OCH2COOH group) is replaced by an . OH radical, leading to the formation of 2,4-dichlorophenol [71]. The formation of this intermediate implies a high degree of selectivity for .…”
Section: Photocatalytic Degradation Of the Target Compoundsmentioning
confidence: 99%